Organic composite hydrogel as well as preparation method and application thereof
By preparing organic composite hydrogels, using orthoesters to carry targeted drugs to escape and self-assemble nanoparticles, the problem of poor enrichment effect of nanodrugs in tumor sites is solved, and efficient delivery and combined treatment of targeted drugs are achieved.
Patent Information
- Application Number
- CN202510627539.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-08-08
- Estimated Expiration
- 2045-05-15
AI Technical Summary
Existing nanodrugs are easily removed after intravenous administration, and the tumor site enrichment effect is poor and the solubility is insufficient, which limits its application in tumor treatment.
The preparation method of organic composite hydrogel is adopted to dissolve the targeted drug in the orthoester and mix it with the oxidized dextran and carboxymethyl chitosan solution to form an organic composite hydrogel. The degradation of the orthoester carries the targeted drug to escape, and self-assemble to form nanoparticles, enhancing the retention ability of the tumor site.
It improves the enrichment ability of targeted drugs in the tumor site, reduces systemic toxic side effects, and achieves the efficient delivery of targeted drugs and the combined synergistic treatment effect.
Smart Images

Figure CN120437041A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomaterial and pharmaceutical preparation preparation, and in particular to an organic composite hydrogel and a preparation method and application thereof. Background Art
[0002] Current drug delivery systems for cancer treatment suffer from numerous limitations, including poor controlled release, easy drug diffusion, weak permeability, inability to accumulate at the tumor site over a long period of time, and insufficient tumor targeting. These shortcomings not only restrict the further development and application of clinical drugs but can also lead to poor therapeutic efficacy and increased systemic toxic side effects. Therefore, it is necessary to identify new drug carriers and modify drug delivery methods to reduce toxic side effects, improve drug delivery efficiency and therapeutic efficacy, and address the issue of poor drug accumulation.
[0003] As an emerging drug delivery system, nanomedicines have demonstrated significant advantages in improving drug solubility, enhancing targeting, prolonging circulation time, achieving sustained and controlled release, reducing toxicity, and enhancing therapeutic efficacy. For example, two targeted drugs, dasatinib and sunitinib, were self-assembled into nanoparticles to enhance their retention at tumor sites. However, these nanomedicines have poor solubility.
[0004] Orthoesters are sensitive, hydrophobic, and biodegradable materials. Since their synthesis, they have been studied for pharmaceutical applications and have been widely used, achieving promising therapeutic results, in drug delivery, protein release, postoperative pain management, and postoperative cancer treatment. Therefore, researchers have used orthoesters to enhance the solubility of nanodrugs. However, current preparation methods still face challenges with easy clearance and poor tumor accumulation after intravenous administration, limiting their widespread application in cancer therapy. Summary of the Invention
[0005] In order to solve the problems of poor solubility of nanomedicines, easy clearance after intravenous administration, and poor enrichment effect at the tumor site, the purpose of the present invention is to provide an organic composite hydrogel and its preparation method and application.
[0006] To achieve the above objectives, the technical solutions of the present invention are as follows.
[0007] The first aspect of the present invention provides a method for preparing an organic composite hydrogel, comprising the following steps: The targeted drug is dissolved in the orthoester to obtain a targeted drug-orthoester solution; the oxidized dextran solution, the targeted drug-orthoester solution and the carboxymethyl chitosan solution are mixed, vortexed and then allowed to stand to obtain an organic composite hydrogel; the concentration of the oxidized dextran solution is 10wt%; the concentration of the carboxymethyl chitosan solution is 5wt%; and the volume ratio of the oxidized dextran solution to the carboxymethyl chitosan solution is 1:0.5-2.
[0008] Preferably, the targeted drugs are dasatinib and sunitinib; and the loading concentration of the targeted drugs in the organic composite hydrogel is 0.01 mg / mL to 20 mg / mL.
[0009] The organic composite hydrogel prepared by this invention exhibits certain injectability and adaptability. After degradation of the hydrogel, the orthoester can efficiently escape with the two targeted drugs. The orthoester contains fluorinated groups, enhancing its penetration into tumor tissue. As the orthoester degrades, the two targeted drugs self-assemble into nanoparticles, enhancing their retention within the tumor site. Once taken up by tumor cells, the two targeted drugs act on different targets, resulting in a synergistic therapeutic effect.
[0010] Preferably, the volume ratio of the oxidized dextran solution, the targeting drug-orthoester solution and the carboxymethyl chitosan solution is 1:1:1; and the dosage ratio of the targeting drug to the orthoester is 8 mg:1 mL.
[0011] The hydrogel formed by oxidized dextran and carboxymethyl chitosan in the present invention can form a three-dimensional network structure with large pores and specific surface area, thereby enabling the hydrogel to effectively carry and release targeted drugs. This high drug loading capacity can not only increase the loading amount of targeted drugs, but also improve the release efficiency. The present invention can achieve precise control of targeted drug release by regulating the structure of the hydrogel, thereby better meeting the demand for accurate targeted drug delivery in tumor treatment.
[0012] Preferably, the chemical structural formula of the orthoester is as follows: .
[0013] Preferably, the molecular weight of carboxymethyl chitosan is 20,000 to 21,000; the degree of carboxyl substitution of carboxymethyl chitosan is 35% to 90%; and the amino unit content of carboxymethyl chitosan is 70% to 90%.
[0014] Preferably, the orthoester is prepared by the following method: 3-amino-1,2-propanediol and ethyl trifluoroacetate are stirred in a solvent system, followed by rotary evaporation, extraction, and drying to obtain an intermediate product 1; and intermediate product 1 is stirred in a solvent system with trimethyl orthoformate in the presence of a catalyst, followed by rotary evaporation, extraction, and drying to obtain the orthoester. Preferably, the molar ratio of 3-amino-1,2-propanediol to ethyl trifluoroacetate is 1:1.5-2; the molar ratio of intermediate product 1 to trimethyl orthoformate is 1:1-4; the solvent is any one of acetonitrile, dichloromethane, chloroform, tetrahydrofuran, and dioxane; the catalyst is p-toluenesulfonic acid; and the molar ratio of intermediate product 1 to catalyst is 1:0.01-0.03.
[0015] Preferably, the oxidized dextran is prepared by the following method: reacting dextran, sodium periodate, and a sodium acetate buffer solution in the dark with stirring, followed by dialysis and lyophilization to prepare the oxidized dextran; the molar ratio of sodium periodate to glucose units in the dextran is 1:1-2; and the molecular weight of the dextran is 60,000-70,000. Preferably, the reaction is carried out in the dark with stirring at room temperature.
[0016] A second aspect of the present invention provides an organic composite hydrogel prepared using the method for preparing the organic composite hydrogel described in the first aspect. The organic composite hydrogel of the present invention can enhance the ability of targeted drugs to accumulate at tumor sites while reducing systemic toxic side effects, thereby achieving a good anti-tumor effect.
[0017] The third aspect of the present invention provides a use of the organic composite hydrogel described in the second aspect in the preparation of a pharmaceutical preparation for anti-tumor or anti-cancer drugs. Preferably, the pharmaceutical preparation is an injectable pharmaceutical preparation.
[0018] Beneficial effects of the present invention: 1. The present invention mainly utilizes a hydrogel formed by oxidized dextran and carboxymethyl chitosan, and at the same time utilizes orthoesters to enhance the solubility of targeted drugs in the hydrogel. The orthoesters can carry targeted drugs and efficiently escape from the hydrogel. During the escape process, as the orthoesters degrade, the targeted drugs can self-assemble to form nanoparticles, thereby enhancing the retention ability of the targeted drugs at the tumor site.
[0019] 2. The present invention utilizes a hydrogel formed by oxidized dextran and carboxymethyl chitosan in combination with orthoesters, which can improve the solubility of targeted drugs in the hydrogel while enhancing the ability to enrich targeted drugs and reducing systemic toxic side effects, thereby solving the problem of poor solubility of nanomedicines, which are still easily cleared after intravenous administration and have poor enrichment effects at the tumor site.
[0020] 3. The preparation method of the present invention is simple, and the material source is wide, which is suitable for promotion and application.
[0021] 4. The organic composite hydrogel prepared by the present invention has certain injectability and adaptability, and realizes the efficient enrichment of targeted drugs at the tumor site, providing a new treatment plan for tumor treatment, while improving the treatment effect and reducing toxic side effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the H NMR spectrum of the orthoester prepared in Example 2.
[0023] Figure 2 The infrared spectra and X-ray diffraction spectra of carboxymethyl chitosan, oxidized dextran, the gel of Example 1, the FOEDS of Example 2, the gel-FOE of Example 3, and the gel-FOEDS of Example 2 are shown. (a) is the infrared spectra; (b) is the X-ray diffraction spectra.
[0024] Figure 3 This is a scanning electron micrograph of the freeze-dried Gel-FOEDS of Example 2.
[0025] Figure 4 Figures (a1) to (a3) show the adhesion test results of the Gel-FOEDS of Example 2 on pigskin; (b1) to (b3) show the adhesion test results of the Gel-FOEDS of Example 2 on pork; and (c1) to (c3) show the adhesion test results of the Gel-FOEDS of Example 2 on pig liver.
[0026] Figure 5 Graphs showing the rheological properties of the Gel-FOEDS of Example 2. Figures A and B show the elastic modulus and viscous modulus of the Gel-FOEDS of Example 2 as a function of time; Figure B shows the shear rate-viscosity curve of the Gel-FOEDS of Example 2; the inset of Figure B is a graph showing the shear rate-viscosity test; Figure C shows the elastic modulus and viscous modulus of the Gel-FOEDS of Example 2 as a function of strain; and Figure D shows the scanning of the elastic modulus and viscous modulus of the Gel-FOEDS of Example 2 alternating between high and low strains.
[0027] Figure 6 This is a graph showing the in vitro degradation rate of Gel-FOEDS in Example 2.
[0028] Figure 7 Graphs showing the in vivo degradation of the Gel-FOEDS of Example 2. (a) to (f) show the comparative in vivo degradation of the Gel-FOEDS of Example 2 on day 0, day 0.5, day 1, day 3, day 5, and day 7.
[0029] Figure 8 This is the H NMR spectrum of the orthoester escaping from the hydrogel.
[0030] Figure 9 Figure 2 is a graph showing the cumulative release rate of the targeted drug in different environments using Gel-FOEDS according to Example 2. A is a graph showing the cumulative release rate of DAS, and B is a graph showing the cumulative release rate of SUN.
[0031] Figure 10 Figure 1 is a graph showing the characterization of targeted drug nanoparticles. A is the particle size distribution of the targeted drug nanoparticles; B is the particle size change of the targeted drug nanoparticles from 0 h to 48 h; and C is the surface zeta potential of the targeted drug nanoparticles as the pH changes.
[0032] Figure 11 Figure 1 is a graph showing the uptake of targeted drugs by tumor cells. (a1) to (a4) show the uptake of Gel-NPs by tumor cells; (b1) to (b4) show the uptake of Gel-FOEDS by tumor cells.
[0033] Figure 12 Figures 2 and 3 are cytotoxicity test images of different experimental groups. A is the cytotoxicity test image of H22 cells in different experimental groups; B is the cytotoxicity test image of HepG2 cells in different experimental groups; C is the cytotoxicity test image of MCF-7 cells in different experimental groups; and D is the cytotoxicity test image of CT26 cells in different experimental groups.
[0034] Figure 13 The distribution of targeted drugs in mice in different experimental groups. (a1) to (a6) are the distribution of targeted drugs in mice from 1 day to 11 days for H2O-ICG; (b1) to (b6) are the distribution of targeted drugs in mice from 1 day to 11 days for FOE-ICG; (c1) to (c6) are the distribution of targeted drugs in mice from 1 day to 11 days for FOEDS-ICG; and (d1) to (d6) are the distribution of targeted drugs in mice from 1 day to 11 days for Gel-FOEDS-ICG.
[0035] Figure 14 This is a diagram showing the blood compatibility test of the hydrogel. Figure 14 The illustration is a photographic record of the centrifuge tube.
[0036] Figure 15 Entity images of mouse tumors in different experimental groups.
[0037] Figure 16 Figure 2 shows the time-dependent changes in tumor volume and body weight of mice in different experimental groups. (a) shows the time-dependent changes in tumor volume and body weight of mice in different experimental groups; (b) shows the time-dependent changes in body weight of mice in different experimental groups.
[0038] Figure 17 Pathological sections of mice in different experimental groups. (a1) to (a6) are pathological sections of the main organs and tumors of mice in the saline control group; (b1) to (b6) are pathological sections of the main organs and tumors of mice in the Gel-NPs group; (c1) to (c6) are pathological sections of the main organs and tumors of mice in the FOEDS group; (d1) to (d6) are pathological sections of the main organs and tumors of mice in the Gel-FOEDS group. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0040] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0041] In the present invention, the molecular weight of carboxymethyl chitosan is 20,000 to 21,000; the degree of carboxyl substitution of carboxymethyl chitosan is 35% to 90%, and the amino unit content of carboxymethyl chitosan is 70% to 90%. Due to batch variability in the production of carboxymethyl chitosan, the structure of the carboxymethyl chitosan in the following examples of the present invention was determined experimentally. Specifically, the carboxymethyl chitosan used in the following examples has a molecular weight of 21,000, a degree of carboxyl substitution of 41.8%, and an amino unit content of 74.7%.
[0042] In the following examples, the methods described are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified. Room temperature is 25°C ± 5°C.
[0043] Example 1 A method for preparing a hydrogel comprises the following steps: Step 1: Weigh 0.0308 mol of dextran powder and 0.0308 mol of sodium periodate and dissolve them in 125 mL of sodium acetate buffer to obtain a mixed solution. The molar ratio of sodium periodate to glucose units in the dextran is 1:2. The molecular weight of dextran is 70,000. The mixed solution is then stirred at room temperature in the dark for 2 hours. After the reaction is complete, the unreacted sodium periodate is quenched with ethylene glycol. The reacted solution is dialyzed in deionized water for 3 days using a 3.5 kD dialysis bag. The dialyzate is then freeze-dried to obtain oxidized dextran, designated as O-Dex.
[0044] In step 2, oxidized dextran was dissolved in water to prepare a 10 wt% oxidized dextran solution, designated as the O-Dex solution. Carboxymethyl chitosan powder with a molecular weight of 21,000 was dissolved in water to prepare a 5 wt% carboxymethyl chitosan solution, designated as the CMCS solution. Testing revealed that the amino unit content of the carboxymethyl chitosan was 74.7%, and the degree of carboxyl substitution was 41.8%.
[0045] In step 3, 10 wt% O-Dex solution and 5 wt% CMCS solution were added to a centrifuge tube in a volume ratio of 2:1, 1:1, and 1:2, followed by mixing, vortexing, and allowing to stand for 30 seconds. After the reaction was complete, a hydrogel was prepared.
[0046] Table 1 Comparison of gelation time of hydrogels prepared with different dosage ratios of O-Dex and CMCS Note: Volume ratio a The volume ratio of the O-Dex solution is 10 wt% and the CMCS solution is 5 wt%.
[0047] The test results showed that the gelation time of the hydrogel decreased with increasing addition of carboxymethyl chitosan solution. When the volume ratio of 10wt% O-Dex solution to 5wt% CMCS solution was 1:1, the hydrogel had a moderate gelation time and good mechanical strength. Therefore, the hydrogel Gel-2 with a volume ratio of 10wt% O-Dex solution to 5wt% CMCS solution of 1:1 was determined to be the hydrogel with the best performance. This was used in subsequent tests and will be collectively referred to as Gel in subsequent tests.
[0048] Example 2 A method for preparing an organic composite hydrogel comprises the following steps: Step 1: Under nitrogen, 0.2 mol of 3-amino-1,2-propylene glycol and 0.3 mol of ethyl trifluoroacetate are added to a three-necked reaction flask, and 150 mL of anhydrous acetonitrile is added as the reaction solvent. The mixture is stirred vigorously for 12 h. After removing the volatile solvent by rotary evaporation under reduced pressure, the crude product is dissolved in ethyl acetate, washed with 10 wt% aqueous sodium carbonate solution and saturated brine, the organic phase is subjected to rotary evaporation under reduced pressure to remove the organic solvent, and then vacuum dried to obtain intermediate product 1. 0.1 mol of intermediate product 1 and 0.4 mol of trimethyl orthoformate are added to a dry reaction flask, and then 0.01 mol of p-toluenesulfonic acid is added as a catalyst, and 150 mL of anhydrous acetonitrile is added as the reaction solvent. The mixture is stirred vigorously for 12 h. After removing the volatile solvent by rotary evaporation under reduced pressure, the crude product is dissolved in ethyl acetate, washed with 10 wt% aqueous sodium carbonate solution and saturated brine, the organic phase is subjected to rotary evaporation under reduced pressure to remove the organic solvent, and then vacuum dried to obtain orthoester, recorded as FOE. The specific reaction equation is as follows:
[0049] .
[0050] Depend on Figure 1 The H NMR spectrum of the present invention proves that the orthoester is successfully synthesized in Example 2.
[0051] In step 2, two targeted drugs, dasatinib and sunitinib, are dissolved in the orthoester prepared in step 1 at a mass ratio of 1:1, and the ratio of the targeted drug to the orthoester is 8 mg:1 mL; a targeted drug-orthoester solution is obtained, which is recorded as FOEDS solution.
[0052] In step 3, 0.0308 mol of dextran powder and 0.0308 mol of sodium periodate were weighed and dissolved in 125 mL of sodium acetate buffer to obtain a mixed solution. The molar ratio of sodium periodate to glucose units in the dextran was 1:2. The molecular weight of dextran was 70,000. The mixed solution was then stirred at room temperature in the dark for 2 hours. After the reaction was complete, the unreacted sodium periodate was quenched with ethylene glycol. The reacted solution was dialyzed in deionized water for 3 days using a 3.5 kD dialysis bag. The dialyzate was then freeze-dried to obtain oxidized dextran, designated as O-Dex.
[0053] In step 4, oxidized dextran was dissolved in water to prepare a 10 wt% oxidized dextran solution, designated as the O-Dex solution. Carboxymethyl chitosan powder with a molecular weight of 21,000 was dissolved in water to prepare a 5 wt% carboxymethyl chitosan solution, designated as the CMCS solution. Testing revealed that the amino unit content of the carboxymethyl chitosan was 74.7%, and the degree of carboxyl substitution was 41.8%.
[0054] In step 5, 10 wt% oxidized dextran solution, FOEDS solution, and 5 wt% carboxymethyl chitosan solution were added to a centrifuge tube in a volume ratio of 1:1:1, mixed, vortexed, and allowed to stand for 30 seconds. After the reaction was complete, an injectable organic composite hydrogel was prepared, designated Gel-FOEDS. The targeted drug loading concentration in the organic composite hydrogel was 10 mg / mL.
[0055] Example 3 A method for preparing an organic composite hydrogel, which differs from Example 2 in that step 2 is omitted. The specific preparation method is: prepare an orthoester according to the preparation method of Example 2, which is recorded as FOE. Prepare oxidized dextran according to the preparation method of Example 2, and configure it into an oxidized dextran solution with a concentration of 10wt%. Configure a carboxymethyl chitosan solution with a concentration of 5wt%. According to a volume ratio of 1:1:1, 10wt% O-Dex solution, orthoester and 5wt% CMCS solution are added to a centrifuge tube in sequence, mixed, vortexed and allowed to stand for 30s. After the reaction is completed, an injectable organic composite hydrogel is prepared, which is recorded as Gel-FOE. The drug loading concentration of the targeted drug in the organic composite hydrogel is 10mg / mL.
[0056] Example 4 A method for preparing an organic composite hydrogel differs from that of Example 2 in that the FOEDS solution prepared in steps 1 and 2 is replaced with a targeted drug solution. The specific preparation method is as follows: oxidized dextran is prepared according to the preparation method of Example 2 and configured into an oxidized dextran solution with a concentration of 10 wt%. A carboxymethyl chitosan solution with a concentration of 5 wt% is configured. Dasatinib and sunitinib, two targeted drugs, are mixed in a mass ratio of 1:1, dissolved in dimethyl sulfoxide, and then the dimethyl sulfoxide is removed by dialysis. The mixture is then added to the 10 wt% oxidized dextran solution and the 5 wt% carboxymethyl chitosan solution in an equal volume ratio, vortexed, and allowed to stand for 30 seconds. After the reaction is completed, an organic composite hydrogel is prepared, which is referred to as Gel-NPs. The drug loading concentration of the targeted drug in the organic composite hydrogel is 10 mg / mL.
[0057] Next, the performance of the hydrogel and organic composite hydrogel prepared in the above examples was tested.
[0058] Carboxymethyl chitosan is the full name of carboxymethyl chitosan, abbreviated as CMCS. Oxidized dextran is the full name of oxidized dextran, abbreviated as O-Dex. Orthoesters are abbreviated as FOE. Dasatinib is the full name of dasatinib, abbreviated as DAS. Sunitinib is the full name of sunitinib, abbreviated as SUN. Targeted drug orthoesters are abbreviated as FOEDS.
[0059] Test 1: Infrared spectrum test.
[0060] Carboxymethyl chitosan, oxidized dextran, the Gel of Example 1, the FOEDS of Example 2, the Gel-FOE of Example 3, and the Gel-FOEDS of Example 2 were used as samples to be tested. -1 ~4000cm -1 The infrared spectrum test was carried out at the wavelength of Figure 2 Figure (a).
[0061] Depend on Figure 2 As can be seen from Figure (a), the oxidized dextran -1 The characteristic peak at 1635cm is the stretching vibration peak of the -C=O bond on the aldehyde group, indicating that after the oxidation of dextran, part of the hydroxyl groups on the structure have become aldehyde groups, indicating that the oxidation of dextran is successful. -1 A new absorption peak also appeared, attributed to the imino bond -C=N-, demonstrating that carboxymethyl chitosan and oxidized dextran underwent Schiff base crosslinking. These results demonstrate that Example 2 of the present invention successfully prepared oxidized dextran, and that the Schiff base crosslinking reaction between oxidized dextran and carboxymethyl chitosan resulted in the preparation of an organic composite hydrogel.
[0062] Test 2: X-ray diffraction test.
[0063] Carboxymethyl chitosan, oxidized dextran, the Gel of Example 1, the FOEDS of Example 2, the Gel-FOE of Example 3, and the Gel-FOEDS of Example 2 were used as test samples and subjected to X-ray diffraction tests at an angle range of 5° to 80°.
[0064] like Figure 2 As shown in Figure (b), carboxymethyl chitosan exhibits a sharp peak at 20.5°; O-Dex exhibits a broad peak at 21.7°; and Gel exhibits a broad peak at 22.8°. This indicates that O-Dex and CMCS undergo cross-linking, and the formation of covalent bonds alters the crystal structure, confirming the successful preparation of the organic composite hydrogel. Furthermore, the broad peaks for FOEDS, Gel-FOE, and Gel-FOEDS are located at the same position, demonstrating the correct structure of the organic composite hydrogel and that the introduction of the orthoester and targeted drug did not alter the structure of the organic composite hydrogel. The mass difference before and after hydrogel formation was measured using the freeze-drying method, and the cross-linking degree of the hydrogel was calculated to be 80.9%.
[0065] Test 3: Scanning electron microscopy observation.
[0066] Carboxymethyl chitosan and oxidized dextran were used to form a gel by Schiff base reaction. After the morphology of the Gel-FOEDS of Example 2 was stable and did not change, a camera was used to record the macroscopic state of the hydrogel. The Gel-FOEDS was quickly frozen with liquid nitrogen and then subjected to a brittle fracture treatment, and then placed in a freeze dryer for freeze drying. Take the freeze-dried Gel-FOEDS, cut a portion of the thin slice from the brittle fracture surface, and with the brittle fracture surface facing up, use conductive tape to stick the brittle fracture surface to the surface of the silicon wafer, and then stick the silicon wafer to the edge of the sample stage. After the sample was sprayed with gold, it was observed using a scanning electron microscope.
[0067] like Figure 3 As shown, the microstructure of the Gel-FOEDS of Example 2 was observed using a scanning electron microscope. It can be seen that the freeze-dried Gel-FOEDS presents a regular and dense porous structure.
[0068] Test 4: Adhesion test.
[0069] To verify that the organic composite hydrogel Gel-FOEDS of Example 2 has good adhesion, different animal tissues, such as skin, muscle, and liver, were selected for adhesion testing. Different materials, such as metal, plastic, glass, and rubber materials, were then selected for testing. The Gel-FOEDS was attached to the surfaces of the above-mentioned different materials, and its adhesion was recorded with a camera.
[0070] like Figure 4 As shown, the Gel-FOEDS of Example 2 adhered well to various animal tissue surfaces, such as pigskin, pork, and pig liver, and remained firmly attached to the tissue surface after being twisted, flipped, and folded. This indicates that the reason for the good adhesion of the Gel-FOEDS of Example 2 is that non-covalent forces such as hydrogen bonds are easily generated between the Gel-FOEDS and different materials.
[0071] Test 5: Elastic modulus and viscous modulus test and shear thinning ability test.
[0072] The organic composite hydrogel Gel-FOEDS of Example 2 was tested using a rotational rheometer. A single frequency sweep was performed on the Gel-FOEDS to measure its elastic modulus and viscous modulus at constant temperature and constant stress. The elastic modulus is denoted as G', and the viscous modulus is denoted as G". The Gel-FOEDS was subjected to a shear rate sweep with a sweep range of 0.1 s. -1 ~100s -1The shear thinning ability of Gel-FOEDS was measured, which is an important indicator for determining the injectability of Gel-FOEDS. Finally, the critical strain of Gel-FOEDS was found by applying strains of 1% to 200%. Then, alternating high and low strain scans were used to detect changes in G' and G", thereby examining the self-healing properties of Gel-FOEDS.
[0073] like Figure 5 In Figure A, G' of the Gel-FOEDS in Example 2 is consistently greater than G", indicating that the Gel-FOEDS is in a gel state and gradually stabilizes over time. Shear thinning refers to the phenomenon in which the apparent viscosity of a non-Newtonian fluid decreases with increasing shear rate. This is due to changes in the fluid's internal structure when subjected to shear forces, resulting in a decrease in viscosity. This property is extremely important for applications such as gel injection and drug delivery.
[0074] like Figure 5 As shown in Figure B, as the shear rate increases, the viscosity decreases until it stabilizes, and the Gel-FOEDS can pass through the syringe needle smoothly, indicating good injectability. By increasing the oscillating strain at a constant frequency and observing the changing trends of G' and G", it can be found that the critical strain required to destroy the gel network and transition to a solution state is 101.2%, as shown in Figure 2. Figure 5 The C graph is used as the standard to determine the alternating scanning of high strain (150%) and low strain (1%). Figure 5 Figure D shows that at high strain, G” is greater than G’, indicating that the Gel-FOEDS is in a sol state. At low strain, G” is less than G”, indicating that the Gel-FOEDS has a gel state. This change occurs repeatedly with the alternation of high and low strains, indicating that the Gel-FOEDS has certain self-healing properties.
[0075] Test 6: In vitro degradation test.
[0076] The organic composite hydrogel Gel-FOEDS prepared in Example 2 was weighed as M1, and then placed in phosphate buffer solutions of pH = 7.4, 6.8 and 5.0, respectively. Three parallel controls were set for each group and placed in a 37° constant temperature shaker. At the preset time points of 0h, 1h, 3h, 6h, 12h, 24h, 48h, 72h, 96h and 120h, the phosphate buffer solution was aspirated with a syringe, and the remaining Gel-FOEDS was weighed and recorded as M1. r The remaining mass ratio of Gel-FOEDS was calculated by the following formula:
[0077] Residual mass ratio = (Mr / M1)×100%; where M r is the mass of the remaining Gel-FOEDS; M1 is the mass of the initial Gel-FOEDS.
[0078] Gel-FOEDS was added to buffer solutions of pH = 5.0, 6.8 and 7.4, respectively. Figure 6 As shown in the figure, under different pH conditions, Gel-FOEDS absorbs water and swells within the first hour, causing its mass to increase. Subsequently, the swelling stops and the Gel-FOEDS begins to degrade gradually. The degradation rate is rapid within the first 48 hours, followed by a slow degradation. Furthermore, the degradation rate of Gel-FOEDS at pH 5.0 is greater than that at pH 6.8 and pH 7.4. This is primarily due to the fact that the hydrolysis rate of the imine bond is affected by the ambient pH; the stronger the acidity, the faster the degradation rate.
[0079] Test 7: In vivo degradation test.
[0080] An equal amount of Gel-FOEDS stained with methylene blue was subcutaneously injected into the chest of mice using a syringe. The mice were dissected at preset time points, 0 days, 0.5 days, 1 day, 3 days, 5 days, and 7 days, and the degradation of the organic composite hydrogel was recorded with a camera.
[0081] As time goes by, the volume of Gel-FOEDS gradually decreases, indicating that the degradation of Gel-FOEDS is good, which is conducive to the stable release of targeted drugs.
[0082] Figure 7 The in vivo degradation observation results showed that Gel-FOEDS was almost completely degraded on the third day, and the in vivo degradation rate was higher than the in vitro degradation rate. This may be because the action of enzymes in the body and the change of pH accelerated the collapse of the gel network, resulting in a greater degradation rate in vivo than in vitro.
[0083] First, prepare phosphate buffer solutions of pH=6.8 and 7.4, immerse the Gel-FOEDS in the buffer solution and place it in a 37° constant temperature shaker. At the preset time points, take out the Gel-FOEDS and slice it in different areas. Observe the morphological changes of FOE under a microscope, and take part of the buffer solution for freeze-drying at 0.5h, 1h, and 1.5h. 1 The degradation of FOE was detected by H NMR.
[0084] like Figure 8As shown in the figure, FOE was detected in the buffer solution and gradually degraded over time, becoming almost completely degraded at 1.5 hours. This result indicates that FOE can escape from the organic composite hydrogel and that the presence of fluorinated groups in the FOE structure enhances the penetration of the two targeted drugs into tumor tissue.
[0085] Test 8: Drug Release Rate Analysis.
[0086] First, 0.2 M phosphate buffer solutions with pH values of 7.4, 6.8, and 5.0 were prepared. 1 mL of Gel-FOEDS was added to a dialysis bag with a molecular cutoff of 3500 Da. The dialysis bag was then immersed in 5 mL of 0.2 M phosphate buffer solutions of different ratios. New buffer solutions were replaced at preset time points, and the cumulative release rates of DAS and SUN were detected using a multifunctional microplate reader.
[0087] like Figure 9 As shown in Figure A, on the fifth day, under the condition of pH = 5.0, the cumulative release rate of SUN reached 83%, while under the conditions of pH = 6.8 and pH = 7.4, the cumulative release rates were 61% and 56%, respectively.
[0088] like Figure 9 As shown in Figure B, on the fifth day, the cumulative release rate of DAS reached 82% at pH 5.0, while at pH 6.8 and pH 7.4, the cumulative release rates were 63% and 60%, respectively. This is because the imine bond network in the organic composite hydrogel collapses at different rates under different pH conditions, allowing DAS and SUN to continuously escape from the organic composite hydrogel, thereby achieving sustained release of targeted drugs.
[0089] Test 9: Hydrated particle size, polydispersity index and surface Zeta potential test.
[0090] Gel-FOEDS were immersed in 0.2 M phosphate buffer solutions at pH 5.0, 6.8, and 7.4 and placed in a shaker at 100 rpm and 37°C. The extract was aspirated at pre-set time points of 0 h, 3 h, 6 h, 12 h, 24 h, and 48 h, and fresh buffer was added. Dynamic light scattering was used to determine the hydrated particle size, polydispersity index, and surface zeta potential of the extracts, with three replicates for each sample.
[0091] At pH 6.8, the nanoparticle size was measured using dynamic light scattering for 96 hours. The experiment was conducted in three groups, and the results were averaged. The extract was then freeze-dried, and the microstructure and size were observed and measured using a transmission electron microscope.
[0092] like Figure 10As shown in Figure A, the average particle size was measured to be 163.8 nm. Transmission electron microscopy was then used to detect the presence of targeted drug nanoparticles, further verifying that the targeted drug could escape from Gel-FOEDS in the form of nanoparticles. Figure 10 As shown in Figure B, the targeted drug nanoparticles in the extract were detected at the preset time points, and their particle size remained almost unchanged, indicating that the targeted drug nanoparticles can remain stable under normal physiological conditions. Figure 10 As shown in Figure C, as the pH value decreases, the surface potential gradually increases. This is due to the protonation of amino groups on the surface of targeted drug nanoparticles, which is conducive to the uptake of targeted drug nanoparticles by tumor cells.
[0093] In summary, targeted drug nanoparticles can indeed successfully escape from Gel-FOEDS and remain stable under physiological conditions. Moreover, the protonation effect of targeted drug nanoparticles under acidic conditions can enhance their uptake by tumor cells, thereby exerting an anti-tumor effect.
[0094] Test 10: Qualitative uptake by cells.
[0095] H22 mouse liver cancer cells, referred to as H22 cells. The full name of 4',6-diamidino-2-phenylindole is 4',6-diamidino-2-phenylindole, referred to as DAPI. H22 cells were washed, digested, and pipetted into RPMI-1640 cell culture medium. H22 cells and HepG2 cells were cultured at 1×10 per well. 5 Cells were seeded at a density of 100 μL in six-well plates and cultured. They were then placed in a sterile, thermostatic incubator for further culture. After the cells adhered, 200 μL of Gel-NPs and 200 μL of Gel-FOEDS were added to each well and incubated for another 8 hours. Following incubation, the cells were digested and collected, fixed with 4% paraformaldehyde for 10 minutes. After fixation, the paraformaldehyde was aspirated and the cells were rinsed with PBS. The cell nuclei were then stained with DAPI for 10 minutes. Finally, confocal laser scanning microscopy was used for detection and imaging. The successful uptake of targeted drugs by tumor cells is crucial for successful treatment. H22 cells were used to evaluate their ability to take up targeted drugs in the slightly acidic extracellular environment of pH 6.8. DAS produces an aggregated luminescence effect, which can be used to track intracellular drugs.
[0096] like Figure 11 As shown in the figure, obvious green fluorescence can be observed in the cells after 4 hours, and the targeted drug uptake ability of the final group Gel-FOEDS is significantly stronger than that of Gel-NPs due to the presence of FOE. This is because the FOE structure contains fluorinated groups, which enhances its permeability.
[0097] Test 11: The MTT assay was used to evaluate the in vitro activity of the organic composite hydrogel.
[0098] The tumor cells used in the experiment were H22, HepG2, MCF-7 and CT26 cells. The experimental groups were set as Gel, Gel-NPs, FOEDS and Gel-FOEDS. The concentration gradient of targeted drug nanoparticles was 5μM, 10μM, 20μM, 40μM and 80μM. Gel is a blank hydrogel without nanoparticles, and the concentrations of its components, carboxymethyl chitosan and oxidized dextran, are the same as those of Gel-FOEDS. The experiment used 96-well plates, and the experimental process was strictly carried out in a sterile operating table. In order to further evaluate the in vitro anti-tumor activity of organic composite hydrogels, H22, HepG2, MCF-7 and CT26 were selected to construct tumor cell models, and incubated with different concentrations of drugs in different groups for 48 hours.
[0099] like Figure 12 As shown in Figures A to D, the cell survival rates of the blank hydrogel group were all above 80%, indicating that the blank hydrogel Gel has good biosafety. However, as the concentration of orthoester increases, the cell survival rate is lower than 50%, indicating that orthoester has certain cytotoxicity. This is because the degradation products of orthoester are toxic and cause cell death. The cytotoxicity of the Gel-FOEDS group is stronger than that of the Gel-NPs group. Since the orthoester contains fluorinated groups in the organic composite hydrogel, the penetration ability of the targeted drug in the tumor tissue is enhanced, thereby allowing more targeted drugs to be taken up by cells. Therefore, the Gel-FOEDS group has higher cytotoxicity, proving that the Gel-FOEDS of Example 2 of the present invention has good in vitro anti-tumor activity.
[0100] Test 12: Observe the distribution of targeted drugs in the tumor site of mice.
[0101] The tumor volume was 200 mm 3 The mice were depilated under their left armpits and divided into four groups. H2O-ICG, FOE-ICG, FOEDS-ICG, and Gel-FOEDS-ICG were injected into the tumor site of the mice at an injection dose of 2.5 mg / kg. At the preset time points of 1d, 3d, 5d, 7d, 9d, and 11d, the distribution of targeted drugs in the tumor site of the mice was observed using a multimodal in vivo imaging device and photographed and recorded.
[0102] Preparation of H2O-ICG: Dissolve indocyanine green in water to obtain an indocyanine green aqueous solution, denoted as H2O-ICG; wherein the concentration of indocyanine green is 1 mg / mL.
[0103] Preparation of FOE-ICG: Indocyanine green and orthoester were mixed uniformly to obtain an indocyanine green-orthoester solution, denoted as FOE-ICG; wherein the concentration of indocyanine green was 1 mg / mL.
[0104] Preparation of FOEDS-ICG: DAS, SUN, and indocyanine green were mixed in a mass ratio of 1:1:1, and the orthoester was added, vortexed, and sonicated to obtain an indocyanine green-targeted drug-orthoester solution, designated as FOEDS-ICG; the indocyanine green concentration was 1 mg / mL.
[0105] Preparation of Gel-FOEDS-ICG: Following the method of Example 2, DAS, SUN, and indocyanine green were mixed in a mass ratio of 1:1:1, and then the orthoester was added to obtain an indocyanine green-targeted drug-orthoester solution, wherein the indocyanine green concentration was 1 mg / mL. The indocyanine green-targeted drug-orthoester solution was then added dropwise to a 10 wt% oxidized dextran solution, and finally, a 5 wt% carboxymethyl chitosan solution was added to form a gel; the volume ratio of the oxidized dextran solution to the carboxymethyl chitosan solution was 1:1, to prepare an organic composite hydrogel, designated Gel-FOEDS-ICG. The targeting drug loading concentration in the organic composite hydrogel was 10 mg / mL.
[0106] In order to explore the enrichment of targeted drugs in mouse tumor sites, H2O-ICG, FOE-ICG, FOEDS-ICG, and Gel-FOEDS-ICG were injected into the mouse tumor sites in situ with an in situ injection dose of 100 μL, and their fluorescence intensity was observed by a multi-mode in vivo imaging instrument.
[0107] like Figure 13 As shown in the figure, H2O-ICG diffuses rapidly in the tumor site, and the fluorescence disappears on the fifth day, and the retention time in the tumor site is short. Since orthoesters can enhance the penetration of targeted drugs in the tumor site, the retention time of FOE-ICG is longer than that of H2O-ICG. Figure 13 As can be seen in the figure, the fluorescence intensity of both FOEDS-ICG and Gel-FOEDS-ICG shows a trend of first increasing and then decreasing. The fluorescence of the Gel-FOEDS-ICG group persists longest at the tumor site, demonstrating the best retention. This conclusion is also confirmed by the fluorescence decay trend graph in the figure. In summary, the organic composite hydrogel can enhance the accumulation of targeted drugs at the tumor site, thereby enabling the sustained release of targeted drugs to kill tumors.
[0108] Test 13: Hemolytic Activity Assessment. Hemolysis occurs when red blood cells are damaged in vitro or in vivo, leading to the release of intracellular hemoglobin, causing a hemolytic reaction that can be fatal in severe cases. Therefore, before conducting in vivo anti-tumor experiments, it was necessary to conduct a hemolytic activity assessment on the organic composite hydrogel Gel-FOEDS from Example 2 to test its hemocompatibility. The specific steps were as follows: First, 500 μL of mouse whole blood was collected, a small amount of sodium heparin was added to prevent blood clotting, and the blood was dispersed into 5 mL of PBS buffer. The blood was centrifuged at 2500 rpm for 5 minutes, and the red blood cells in the lower layer were collected. The above steps were repeated until the supernatant was clear. The red blood cells were then collected and evenly dispersed into 10 mL of normal saline to prepare a red blood cell suspension for later use. Experimental Group: 500 μL of the red blood cell suspension was mixed with Gel-FOEDS samples at varying concentrations ranging from 31.25 μg / mL to 1000 μg / mL and incubated at 37°C for 1 hour. Positive control group: 500 μL of cell suspension was mixed with 500 μL of deionized water and incubated at 37°C for 1 hour. Negative control group: 500 μL of cell suspension was mixed with 500 μL of normal saline and incubated at 37°C for 1 hour. After incubation, centrifuge at 10,000 rpm for 5 minutes, arrange the centrifuge tubes in a row and take a photo. 200 μL of supernatant was added to a 96-well cell culture plate, and the absorbance of each well was measured at a UV wavelength of 570 nm using a multifunctional microplate reader and recorded. The hemolysis rate was calculated using the following formula:
[0109] Hemolysis rate (%) = (OD 样品组 -OD 阴性对照组 / OD 阳性对照组 -OD 阴性对照组 )×100%; where OD 样品组 Indicates the absorbance value of the experimental group; OD 阴性对照组 Indicates the absorbance value of the negative control group; OD 阳性对照组 Represents the absorbance value of the positive control group.
[0110] like Figure 14 As can be seen, in the positive control group, red blood cell membranes ruptured, hemoglobin was released, and the supernatant was distinctly red. In contrast, in the experimental groups treated with different concentrations of Gel-FOEDS, the supernatants were clear and showed no significant hemolysis compared to the negative control group. The absorbance of each experimental group was measured using a multifunctional microplate reader at a wavelength of 540 nm. The hemolysis rate calculated using the hemolysis rate calculation formula was less than 5% for each experimental group, demonstrating the high blood compatibility and good biosafety of the organic composite hydrogel of Example 2.
[0111] Test 14: In vivo anti-tumor experiment. The experiment used male ICR mice with a body weight range of 18g to 22g, and all animals strictly abided by the experimental animal management regulations. The specific operation is as follows: Take the H22 cell line, inject it into the mouse abdominal cavity and culture it for 7-10 days, then extract the mouse ascites and transfer it to a 10mL sterile centrifuge tube, centrifuge to remove the supernatant and wash it three times with sterile PBS solution until the upper layer is clear, and then use sterile saline to redisperse the cells. It can be obtained by trypan blue staining and blood cell counting that the cell survival rate is greater than 95%, and then the cells are diluted with saline to about 1 million / mL, and the diluted cell suspension is inoculated into the left armpit of the mouse with a syringe. The injection volume is about 100μL, and the tumor volume is in the range of 180mm 3 -220mm 3 When the tumor volume is less than 100 μg / cm2, the tumor volume can be calculated according to the following formula: tumor volume (mm 3 ) = A × B 2 / 2; A is the long diameter of the tumor; B is the short diameter of the tumor. When the tumor volume of the mouse grows to 200mm 3 The mice were randomly divided into 4 groups, with 6 mice in each group. Normal saline control group: Normal saline was injected orally into the tumor site of the mice. The normal saline control group was recorded as the Control group. Gel-NPs group: Gel-NPs were injected orally into the tumor site of the mice. FOEDS group: FOEDS was injected orally into the tumor site of the mice. Gel-FOEDS group: Gel-FOEDS was injected orally into the tumor site of the mice.
[0112] DAS was administered once on days 1, 3, and 6, with a dose of 20 mg / kg. Mice were then observed for 12 days, with body weight and tumor volume recorded daily. After 12 days, the mice were sacrificed and dissected to obtain major organs (heart, liver, spleen, lung, kidney), as well as tumor tissue. The removed tumor tissue was weighed and photographed. The removed organ tissues and tumors were fixed with 4% paraformaldehyde and stained with hematoxylin & eosin. Sections were then examined under an inverted microscope to assess the extent of damage.
[0113] In this example, a mouse liver cancer tumor model was constructed to verify the anti-tumor effect of the organic composite hydrogel in vivo. DAS was injected orally into the tumor site of the mice on days 1, 3, and 6, at a dose of 20 mg / kg.
[0114] like Figure 15 From the tumor solid images of mice, it can be seen that compared with the normal saline control group, the Gel-NPs, FOEDS, and Gel-FOEDS groups all inhibited the tumor to varying degrees.
[0115] The curve of mouse tumor volume change over time, such as Figure 16 (a) shows that at day 12, the tumor volume of mice in the saline control group reached 1420 mm 3 The tumor volume of the Gel-NPs group was approximately 290 mm 3 , while the tumor volume of the Gel-FOEDS group was approximately 160 mm 3 , indicating that the Gel-FOEDS group has a more obvious anti-tumor effect. This is because the organic composite hydrogel is enriched in the tumor site for a long time, and the orthoester enhances the penetration of targeted drugs in the tumor site, so the anti-tumor effect is better.
[0116] The weight change curve of mice at 12 days, such as Figure 16 As shown in Figure (b), the mice showed no significant changes in weight and were in good condition with no obvious toxic side effects, indicating that the organic composite hydrogel of Example 2 promoted the long-term enrichment of targeted drugs at the tumor site, thereby reducing systemic toxicity.
[0117] Analyze the results of hematoxylin & eosin staining. Pathological sections of the main organs and tumors of mice stained with hematoxylin & eosin, such as Figure 17 .
[0118] Depend on Figure 17 It can be seen that compared with the saline control group, the tumor sections of Gel-NPs and FOEDS showed varying degrees of damage, and the degree of damage in the Gel-FOEDS group was greater. This is because the organic composite hydrogel Gel-FOEDS can achieve long-term enrichment of targeted drugs at the tumor site, and the penetration-promoting function of the orthoester enhances its anti-tumor effect, with a more obvious tumor-killing effect. Compared with the saline group, the main organ tissues of the mice, the heart, liver, spleen, lungs and kidneys, did not show obvious damage. This further verifies that the organic composite hydrogel prepared in Example 2 of the present invention can be retained at the tumor site for a long time, thereby achieving long-term enrichment of targeted drugs at the tumor site and having good biosafety.
[0119] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an organic composite hydrogel, characterized in that: The following steps are involved: dissolving the targeted drug in the orthoester to obtain a targeted drug-orthoester solution; The oxidized dextran solution, the targeted drug-orthoester solution and the carboxymethyl chitosan solution were mixed, vortexed and then allowed to stand to obtain an organic composite hydrogel; The concentration of the oxidized dextran solution was 10 wt %; the concentration of the carboxymethyl chitosan solution was 5 wt %; The volume ratio of the oxidized dextran solution to the carboxymethyl chitosan solution is 1:0.5-2.
2. The method for preparing the organic composite hydrogel according to claim 1, wherein: The targeted drugs are dasatinib and sunitinib; the loading concentration of the targeted drugs in the organic composite hydrogel is 0.01 mg / mL to 20 mg / mL.
3. The method for preparing the organic composite hydrogel according to claim 1, wherein: The volume ratio of oxidized dextran solution, targeted drug-orthoester solution and carboxymethyl chitosan solution is 1:1:1; the dosage ratio of targeted drug to orthoester is 8 mg:1 mL.
4. The method for preparing the organic composite hydrogel according to claim 1, wherein: The molecular weight of carboxymethyl chitosan is 20,000 to 21,000; the degree of carboxyl substitution of carboxymethyl chitosan is 35% to 90%; and the amino unit content of carboxymethyl chitosan is 70% to 90%.
5. The method for preparing the organic composite hydrogel according to claim 1, wherein: Orthoesters are prepared by the following method: 3-amino-1,2-propanediol and ethyl trifluoroacetate are stirred and reacted in a solvent system, and then subjected to rotary evaporation, extraction, and drying to obtain intermediate product 1; Under the action of a catalyst, the intermediate product 1 and trimethyl orthoformate are stirred and reacted in a solvent system, and the orthoester is obtained by rotary evaporation, extraction and drying.
6. The method for preparing the organic composite hydrogel according to claim 5, characterized in that: The molar ratio of 3-amino-1,2-propanediol to ethyl trifluoroacetate is 1:1.5-2; The molar ratio of intermediate 1 to trimethyl orthoformate is 1:1-4; The solvent is any one of acetonitrile, dichloromethane, chloroform, tetrahydrofuran, and dioxane; The catalyst is p-toluenesulfonic acid; The molar ratio of the intermediate product 1 to the catalyst is 1:0.01-0.
03.
7. The method for preparing the organic composite hydrogel according to claim 1, wherein: Oxidized dextran is prepared by the following method: Dextran, sodium periodate and sodium acetate buffer solution are reacted in the dark with stirring, and after the reaction is completed, the reaction is dialyzed and freeze-dried to prepare oxidized dextran; The molar ratio of sodium periodate to glucose units in dextran is 1:1-2; The molecular weight of dextran is 60,000 to 70,000.
8. An organic composite hydrogel, characterized in that The organic composite hydrogel is prepared by the preparation method of any one of claims 1 to 7.
9. Use of the organic composite hydrogel according to claim 8 in preparing a pharmaceutical preparation for anti-tumor or anti-cancer drugs.
10. The use according to claim 9, characterized in that The pharmaceutical preparation is an injectable pharmaceutical preparation.
Citation Information
Patent Citations
Preparation method of carboxymethyl chitosan pH sensitive hydrogel drug carrier
CN106860871A
Nano-hydroxyapatite composite hydrogel as well as preparation method and application thereof
CN115322451A
Gel formulations for topical drug release
CN115501172A
Tumor microenvironment response type nano composite hydrogel co-drug delivery system and preparation method thereof
CN116672303A
Biomimetic nanoparticle suspension formulation based on orthoester compound and preparation method thereof
CN119770428A
Cited By
Chinese herbal medicine component for relieving neurodegenerative diseases and preparation method thereof
CN120899655A